El reconocimiento en comunicación/educación. Esbozos para una categoría en construcción - Martínez, Darío Gabriel (CIICLA, Universidad de Costa Rica, 2017)
This article presents notions about recognition. The contributions of Axel Honneth, Nancy Fraser and Paul Ricoeur are taken as a starting point. These conceptual positions are combined to reflect on a category of communication/education. The problem of recognition has always been present in this field. Named in one way or another, this question poses a possible recurrence that is to ask about concrete intervention in political-cultural fields, institutions and organizations. For this, it is considered how it has been worked in this field from the works of Paulo Freire and Jorge Huergo.